Pengaruh Work-Life Balance dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada PT. Sentratek Adi Mitra Jakarta Utara - Maylinda Asriyah (EBISMAN eBisnis Manajemen, 2026)
Human resource management plays an important role because human resources are the main asset in determining the success of an organization. This study aims to analyze the effect of work-life balance and work environment on employee job satisfaction at PT. Sentratek Adi Mitra, North Jakarta. The research sample consisted of 35 employees selected using non-probability sampling techniques with a saturated sampling method. This study used a quantitative method with primary data obtained through observation and questionnaires. Data analysis was performed using IBM SPSS Statistics version 27 through validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and coefficient of determination (R²) tests. The results showed that work-life balance had a positive and significant effect on employee job satisfaction with a t-value of 5.526 > t-table 2.037 and a sig. value of 0.000 < 0.05. The work environment also has a positive and significant effect on job satisfaction with a t-value of 3.421 > t-table 2.037 and a sig. value of 0.002 < 0.05. Simultaneously, work-life balance and work environment have a positive and significant effect on employee job satisfaction with an F test result of 39.372 > 3.28 and a significance value of 0.000 < 0.05.